THE FLOUTING MAXIMS OF HUMOROUS LYING IN â€œHOW I MET YOUR MOTHERâ€ TV SERIES - SAFAUDIN, (LANGUAGE HORIZON, 2016)
Abstrak Selain digunakan untuk konteks yang luas dalam kehidupan sehari-hari, kita juga bisa melihat bagaimana kebohongan digunakan sebagai media dalam komedi dengan melihat pada kecenderungannya untuk berputar pada pola tertentu. Hal ini menjadi dasar pada studi ini untuk berfokus padaaktingbohong berkarakteristik humor yang dilakukan oleh karakter dalam serial TV How I Met Your Mother. Tujuan dari studi ini adalah membahas pelanggaran maksim dalam proses bohong pada tataran Implikatur yang dilakukan dalam serial TV How I Met Your Mother selain juga untuk mendeskripsikan kontribusi dari pelanggaran maksim dan imlplikatur dari percakapan terhadap bohong yang ditunjukkan dalam serial TV How I Met Your Mother terkait hal nya dengan memunculkan efek humor. Teori yang digunakan adalah teori implikatur percakapan, prinsip kerjasama, dan mekanisme humor. Data dalam studi ini diambil dari kumpulan percakapan dalam serial TV How I Met Your Mother yang sudah dipilih terlebih dahulu. Studi ini menemukan hubungan yang kuat antara pelanggaran maksim dan implikatur percakapan dalam pembentukan fenomena bohong berkarakteristik humor. Tipe kebohongan tersebut menjadi mudah dikenali dengan adanya  eksploitasi oleh pelanggaran maksim. Sedangkan implikatur percakapan dibutuhkan untuk memahami adanya kebohongan dimana eksploitasi kebohongan berperan sebagai titik kulminasi nya.    Kata Kunci:Bohong, humor, implikatur percakpan, prinsip kerjasama, melanggar maksim Abstract Despite being used in a broad context of daily life, Lying is also seen to be an adequate device to be applied in comedy with a tendency to circulate the process around certain typical patterns. With regard to this fact, this study focuses upon the act of humorous Lying performed by characters of How I Met Your Mother TV Series. The purpose of this study is to examine the conversational maxims which are being flouted during the process of lying within conversational implicature performed at How I Met Your Mother TV Series as well as describing the contribution flouting maxims and conversational implicature toward the lie performed at How I Met Your Mother TV Series in terms of stimulating humorous effect. The theories of Conversational Implicature, Co-operative principles, and humor theories are used within this study. This study also uses descriptive qualitative method as a meant to do the data analysis.The data are set of utterances taken from the dialogue between the characters of How I Met Your Mother TV Series which has been filtered carefully beforehand. This study found that there is a well-established connection between the production of humorous lying with the flouting maxims and conversational implicature theory. Humorous lying are recognized through the exposition of lying in which the surprise element brought by the flouting maxims are somewhat useful in supporting the lying to be exposed. Meanwhile, the conversational implicature is needed in its importance to understand lying as method of asserting in which the exposition of lying is seen to be a culmination point within humorous lying.   Keywords:Lying, humor, conversational implicature, co-operative principles, flouting maxims